Keyhole incision and dissection of tissue above trachea in combination with percutaneous Griggs tracheostomy in patients with abnormal coagulation profile and difficult airway: A life-saving hybrid tracheostomy technique (Indian Journal of Case Reports, 2025)
Tracheostomy is a common requirement in critically ill patients. Many a time, tracheostomy is a lifesaving procedure in critically ill patients with abnormal coagulation profiles or thrombocytopenia, where endotracheal intubation is difficult. Classical surgical tracheostomy has a high risk of bleeding, while the percutaneous technique has a high number of vascular complications and requires a bronchoscope for guiding a percutaneous set needle to puncture the central part of the trachea. Hence, a hybrid technique, keyhole incision and dissection with blunt curved artery forceps up to the pretracheal fascia and Griggs percutaneous technique after direct visualization and palpation of tracheal ring was introduced by Medical intensive care unit team, Department of Medicine, King George’s Medical University, Lucknow India for treating critically ill patients where coagulation profile is deranged and bleeding risk is very high with difficult airway. This hybrid technique was done in a 67-year-old patient with a difficult airway and a deranged coagulation profile after taking proper consent. The procedure was performed with minimal bleeding up to 1–2 mL, without any complication, and also prevents further delay in airway management in emergency without the requirement of specialized instruments (like bronchoscopy or any specialized surgical instrument such as retractor and require minimal assistance in emergency.